Application of reversed-phase liquid-cromatography (RP-HPLC) to direct quantification of 17 (Revista Brasileira de Ciências Farmacêuticas, 2004)
Determination of serum levels of 17±-hydroxyprogeterone (17OHP) is essential for hormonal characterization of the 21-hydroxylase deficiency form of congenital adrenal hyperplasia (CAH). This condition results in female pseudo-hermaphroditism and sexual precocity in both sexes. 17OHP was directly quantified by liquid chromatography and reverse-phase separation (RP-HPLC) in previously ether extracted serum samples. A ODS-Hypersil® column and a water-methanol (4:6; v/v) mobile phase at 1.0 mL/min were employed in the procedure. The 17OHP peak was measured at 246 nm, with a retention time of 5.6 min. The method was effective and efficient with good sensitivity and linearity (r²= 0.9993) in the concentration range of 500 to 100,000 ng/dL. Intra and inter-assay precisions were 4.4 and 8.1%, respectively. This method can be employed in the laboratory routine for 17OHP in the diagnostic evaluation of CAH; RIA must only be employed to quantify values below the 500 ng/dL.